Unmasking conflict in vertical coopetition. Issue 13 (18th May 2021) - Rajala, Anni; Tidström, Annika
Abstract : Purpose: The purpose of this study is to increase understanding about vertical coopetition from the perspective of interrelated conflict episodes on multiple levels. Design/methodology/approach: The empirical part is based on a qualitative single case study of a coopetitive buyer-supplier relationship in the manufacturing sector. Findings: Conflicts in vertical coopetition evolve from being merely functional and task-related to becoming dysfunctional and relationship-related, as the level of competition increases. The nature of conflict episodes influences the development of vertical coopetition, and therefore, the interrelatedness of conflict episodes is important to acknowledge. Practical implications: Although a conflict is considered functional within a company, it may still be dysfunctional as far as the coopetitive relationship with the buyer or seller is concerned. Competition may trigger conflicts related to protecting own technology and knowledge, which may lead to termination of the cooperation, therefore coopetition should be managed in a way that balance sharing and protecting important knowledge to get advantages of coopetition. Originality/value: The findings enhance prior research on vertical coopetition by offering new perspectives on causes of conflicts, their management, outcomes and types. The value of taking a multilevel approach lies in the ability to show how conflicts occur and influence other conflicts through the interrelatedness of conflict elements on different levels.